PERILAKU MEROKOK PADA PASIEN TUBERKULOSIS LAKI-LAKI DI KECAMATAN BANYUWANGI, KABUPATEN BANYUWANGI: Smoking Behavior In Men's Tuberculosis Patients In Banyuwangi District, Banyuwangi District - Rahmasuciani Putri; Susy Sebayang; Septa Puspikawati; Erni Astutik (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2019)
An increasing number of smokers is associated with an increased risk of tuberculosis (TB). The risk of TB can be reduced by two thirds if someone stops smoking. The purpose of this study was to determine smoking behavior in TB patients in three puskesmas in Banyuwangi District (Puskesmas Sobo, Puskesmas Kertosari, and Puskesmas Singotrunan). This research is a descriptive study with a cross-sectional approach, which was conducted for 6 (six) months, June to December 2017. This study used data from a study entitled